Patrimonialisation et durabilité du régime conventionnel territorial à Romans-sur-Isère - Florian Fompérie; Muriel Maillefert; Éva Martinez (Développement Durable et Territoires)
This work questions the links between development projects and territorial conventions, based on an analysis of the territory of Romans-sur-Isère (Drôme, France). A historical study of the characteristics of this model, centered around leather and footwear, shows that two alternative models have emerged over the last thirty years. The first is rather centered on external investments, associated with a « gentrifying » urban renewal model. The second is based more on non-market based values and the patrimonialization of resources around territorial specificities. The latter bears the seeds of an innovative territorial convention that is nevertheless struggling to spread. We suggest, in a programmatic way, original reading keys, around an approach by convention theory. This makes it possible to understand the new forms of territorial value based on the coconstruction of projects and uses.